Representations of *-algebras and many-dimensional dynamical systems - Ostrovskii, V. L.; Turovskaya, L. B. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
The procedure developed earlier for investigation of representations of *-algebras is generalized to a wider class of operator relations. In particular, the developed technique is used for description of all irreducible representations of a nonstandard three-dimensional quantum sphere.